Introducing the crystalline phase of dicalcium phosphate monohydrate - Bing-Qiang Lu (Nature Portfolio, 2020)
Understanding the crystal structure of different calcium phosphates is important for a range of different subjects from geology to biomedicine. Here, the authors report on the synthesis and determination of the crystal structure of dicalcium phosphate monohydrate.